PROBLEMATIKA HUKUM PENJUALAN KEMBALI ASET YANG BELUM LUNAS PEMBAYARANNYA DALAM PEMBIAYAAN MURABAHAH - Luthfiyah Trini Hastuti; Samirah Samirah (Universitas Sebelas Maret, 2014)
This study aims to describe and examine two issues. Firstly, how the murabaha financing in Bank Muamalat Surakarta is. Secondly, how the legal status of the sale of assets that haven’t paid back yet in murabaha financing is.The research method used is a case study with a qualitative-descriptive approach. The scope is limited research focusing on the murabaha financing mechanisms as well as the legal status of the sale of assets that haven’t paid back yet in murabaha financing at Bank Muamalat Surakarta. Types and sources of data are using primary data and secondary data. Primary data contains the result of interviews with Bank Muamalat Surakarta, while secondary data was obtained from books, the internet, financial reports, and other sources.The results of this research is the occurance of murabaha financing which are divided into 3 parts. First of all, the process of submission financing reques, financing analysis process which consist of data collection, guarantee analysis that checks the validation of the guarantee, data verification juridical analysis which is the cheking validation of costumers credibility, and then performs the contract in front of the notary, and the financing process is a process for the disbursement and deposit guarantees. The inclusion of wakalah contract in murabaha in Bank Muamalat Surakarta is inappropriate with fatwa Dewan Syariah Majeleis Ulama Indonesia No.4/DSN-MUI/IV/2000 and Bank Indonesia Regulation No. 7/46/ PB / 2005 due to a wakalah contract made after murabaha contract was.Legal status of the sale of assets that haven’t paid back yet in murabaha financing at Bank Muamalat Surakarta is invalid when the client does not report, and immediately pay off early because there’s specific agreements has been made by the Bank Muamalat Surakarta with the client.